Dynamic Modelling of an Orientable Solar Panel System as a 2-DOF Manipulator - Roldán Mckinley, Javier; Fernández Pizarro, Andrés; Beltrán González, Jaison (Scientia et Technica, 2019)
Lagrange principle is used to derive the dynamic equation of an Orientable Solar Panel System-OSPS. Prior to the dynamic formulation, the OSPS kinematic analysis was eased by considering the system as a 2 degrees-of-freedom open-loop serial manipulator with perpendicular revolute joints. Denavit-Hartenberg parameters let finding the transformation matrix to relate the solar panel with the fixed element was stated. Then, existing formulation about dynamics for serial manipulators was adapted to the OSPS. The explicit dynamic model was used to build a Simunlink block. Another plant was created in SimMechanics. Then, performance of both plants when using the same PID controller were compared for a typical movement of the OSPS system. Results showed agreement for both cases, suggesting that the dynamic model is suitable for further simulations and implementation.